Risk factors associated with positive bacterial culture in salvaged red blood cells during cardiac surgery and postoperative infection incidence: A prospective cohort study - Zhou, Yenong; Chen, Tao; Yang, Chen; Liu, Jincheng; Yang, Xiuling; Zhang, Bing; Jin, Zhenxiao (Frontiers in Medicine, 2023)
Background This study was designed to explore factors associated with the incidence of positive bacterial culture of salvaged red blood cells (sRBCs) recovered with a Cell Saver instrument during cardiac surgery and the impact of such positive outcomes on postoperative infection-related morbidity. Methods The cohort study enrolled 204 patients scheduled for cardiac surgery with intraoperative blood cell salvage and retransfusion from July 2021 to July 2022. These patients were stratified into two groups based on intraoperative sRBCs bacterial culture results: culture (+) and culture (−) groups. Preoperative and intraoperative variables were compared between these groups aim to detect possible predictors of positive culture in sRBCs. In addition, differences in postoperative infection-related morbidity and other clinical outcomes were compared between these groups. Results Of these patients, 49% were sRBCs culture (+), with Staphylococcus epidermidis as the most commonly identified pathogen. Risk factors independently associated with the risk of positive culture in sRBCs included BMI ≥25 kg/m2, a history of smoking, an operative duration ≥277.5 min, the higher number of staff in the operating room and higher surgical case order. Patients in the sRBCs culture (+) group exhibited a longer average ICU stay [3.5 days (2.0–6.0) vs. 2 days (1.0–4.0), P < 0.01], a longer duration of ventilation [20.45 h (12.0–17.8) vs. 13 h (11.0–17.0, P = 0.02)], underwent more allogeneic blood transfusions, exhibited higher transfusion-related costs [2,962 (1,683.0–5,608.8) vs. 2,525 (1,532.3–3,595.0), P = 0.01], and had higher rates of postoperative infections (22 vs. 9.6%, P = 0.02) as compared to patients in the sRBCs culture (−) group. In addition, culture (+) in sRBCs was an independent risk factor for postoperative infection (OR 2.62, 95% CI 1.16–5.90, P = 0.02). Conclusion Staphylococcus epidermidis was the most common pathogen detected in sRBCs in the culture (+) group in this study, identifying it as a potential driver of postoperative infection. Positive sRBCs culture may contribute to postoperative infection and its incidence was significantly associated with patient BMI, history of smoking, operative duration, the number of staff in the operating room and surgical case order.